2019
DOI: 10.1097/pq9.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Lactation Consultation and Early Breast Milk Use in an Outborn NICU

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Positive correlations have been seen in NICUs with dedicated LCs in increasing breastfeeding rates through discharge. [34][35][36][37] In our own institution, we have seen an increase in the percentage of neonates receiving any HM, especially in the outborn population, 37 with the addition of a dedicated LC. We were able to financially support increase in LC staffing by receiving grants from the W.K.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Positive correlations have been seen in NICUs with dedicated LCs in increasing breastfeeding rates through discharge. [34][35][36][37] In our own institution, we have seen an increase in the percentage of neonates receiving any HM, especially in the outborn population, 37 with the addition of a dedicated LC. We were able to financially support increase in LC staffing by receiving grants from the W.K.…”
Section: Discussionmentioning
confidence: 96%
“…[26][27][28][29][30][31][32][33][34][35] Over time, we improved access to lactation consultants (LCs) in labor and delivery (L&D), postpartum and outpatient, included a Spanish-speaking LC, and incorporated an HM cream fortifier, all in an effort to increase the lactation success of these high-risk mothers. 36,37 The primary purpose of this study was to assess the success of our Liquid Gold bundle in the provision of MOM over time, specifically at first enteral feed and at discharge. The secondary aim was to assess the impact of our bundle across racial subgroups to determine whether disparities would persist despite this standardized approach.…”
Section: Introductionmentioning
confidence: 99%
“…In a mixed inborn/referral NICU, Dweck et al (2008) reported that only outborn infants showed increased in-NICU and discharge MOM provision after an IBCLC was hired to see all patients upon admission, but infants with surgical conditions and anomalies, which are typically the population sent to a referral NICU, were excluded. Leeman et al (2019) recently published a quality improvement intervention very similar to ours that took place at a referral children's hospital NICU in which a part-time dedicated IBCLC was hired to supplement hospital-wide lactation service to increase availability of lactation care in the NICU. With proactive approaches like an automatic order for am IBCLC consult for infants admitted at < 48 hr of age, percentage of infants fed MOM on Day 7 of age increased from 76% to 90%; MOM provision throughout hospitalization or at discharge was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The health status of babies at the time of birth, birth weight, age of pregnancy and medications used during pregnancy can influence the ability to start and continue breastfeeding in an effective way 5 .Many newborns, who are followed up and treated in the newborn care unit due to prematurity and other diseases cannot be breastfed directly. In such situations, mothers are required to ensure and maintain milk production via breast pumps 6 . A certain proportion of these babies can be fed with milked breast milk via methods such as feeding with a nasogastric tube, an orogastric tube, a syringe, a dropper and a cup 7 .…”
Section: Introductionmentioning
confidence: 99%